Intergenerational mobility and self-selection on unobserved skills: New evidence - Michael Hebsaker; Guido Neidhöfer; Friedhelm Pfeiffer (Journal for Labour Market Research, 2021)
This study proposes a novel way to examine self-selection on unobserved skills and applies it to a sample of young males seeking asylum in 2015/2016 in Germany. First, the degree of intergenerational mobility of these refugees is assessed, specifically their educational improvement in comparison to their parents' level of education. Next, the estimates are compared with the level of educational mobility of similar-aged males in the refugees' regions of origin. The idea is that this difference indicates the pattern of self-selection on unobserved skills such as grit and motivation. Our findings hint at positive selection on such unobserved skills among these young male refugees.
Keywords: 330; Immigrant selection; Asylum seekers; Human capital; Family background